ENO1 contributes to 5-fluorouracil resistance in colorectal cancer cells via EMT pathway - Gu, Jinrong; Zhong, Kaiqiang; Wang, Longgang; Ni, Haishun; Zhao, Yirui; Wang, Xuchao; Yao, Yizhou; Jiang, Linhua; Wang, Bin; Zhu, Xinguo (Frontiers in Oncology, 2022)
Chemoresistance is one of the main obstacles in the therapy of colorectal cancer (CRC) and many other tumors. ENO1 was associated with various biological characteristics of CRC. This study intended to investigate the function of ENO1 in regulating 5-FU resistance in CRC. In this study, the results indicated that ENO1 was elevated in CRC tissues and associated with poor prognosis of patients. High level ENO1 expression was detected as an independent prognostic factor for overall survival. The expression of ENO1 increased in drug resistant cells (HCT116/5-FU and SW620/5-FU) constructed by increasing concentrations of 5-FU. Knockdown of ENO1 significantly reduced the IC50 and inhibited proliferation and migration ability of HCT116/5-FU and SW620/5-FU. It was found that down-regulation of ENO1 inhibited Epithelial-mesenchymal transformation (EMT) signaling process compared with the control group. Murine xenograft assay confirmed that depletion of ENO1 alleviated 5-FU resistance. In conclusion: This study identified that ENO1 regulated 5-FU resistance through EMT pathway and may provide a novel target for 5-FU resistant CRC in prevention and treatment.